Intravital Imaging of Neocortical Heterotopia Reveals Aberrant Axonal Pathfinding and Myelination around Ectopic Neurons - Li, Alice M (Cereb Cortex, 2021)
Neocortical heterotopia consist of ectopic neuronal clusters that are frequently found in individuals with cognitive disability and epilepsy. However, their pathogenesis remains poorly understood due in part to a lack of tractable animal models. We have developed an inducible model of focal cortical heterotopia that enables their precise spatiotemporal control and high-resolution optical imaging in live mice. Here, we report that heterotopia are associated with striking patterns of circumferentially projecting axons and increased myelination around neuronal clusters. Despite their aberrant axonal patterns, in vivo calcium imaging revealed that heterotopic neurons remain functionally connected to other brain regions, highlighting their potential to influence global neural networks. These aberrant patterns only form when heterotopia are induced during a critical embryonic temporal window, but not in early postnatal development. Our model provides a new way to investigate heterotopia formation in vivo and reveals features suggesting the existence of developmentally modulated, neuron-derived axon guidance and myelination factors.